2017
DOI: 10.1016/j.carbpol.2017.08.127
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of cellulose acetate/polybenzoxazine cross-linked electrospun nanofibrous membrane for water treatment

Abstract: Herein, polybenzoxazine based cross-linked cellulose acetate nanofibrous membrane exhibiting enhanced thermal/mechanical properties and improved adsorption efficiency was successfully produced via electrospinning and thermal curing. Initially, suitable solution composition was determined by varying the amount of the benzoxazine (BA-a) resin, cellulose acetate (CA) and citric acid (CTR) to obtain uniform nanofibrous membrane via electrospinning. Subsequently, thermal curing was performed by step-wise at 150, 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 50 publications
(56 reference statements)
2
40
0
Order By: Relevance
“…Hydrophobic interactions led to a contaminant removal of 97% (Table 20, N2). Cross-linking of cellulose acetate nanofibers with benzene rings by polybenzoxazine provided a hydrophobic adsorptive structure [113]. The adsorbent benzene rings further enabled π-π interactions with Phenantrene aromatic rings, thus leading to 98.5% contaminant removal ( Phenantrene via molecular filtration, by inclusion-complexation of the hydrophobic contaminants in the apolar cyclodextrin cavity [112].…”
Section: Adsorbate Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Hydrophobic interactions led to a contaminant removal of 97% (Table 20, N2). Cross-linking of cellulose acetate nanofibers with benzene rings by polybenzoxazine provided a hydrophobic adsorptive structure [113]. The adsorbent benzene rings further enabled π-π interactions with Phenantrene aromatic rings, thus leading to 98.5% contaminant removal ( Phenantrene via molecular filtration, by inclusion-complexation of the hydrophobic contaminants in the apolar cyclodextrin cavity [112].…”
Section: Adsorbate Propertiesmentioning
confidence: 99%
“…Regarding the adsorption performance, engineered nanofibers yielded over 95% removal efficiency with high adsorption capacities comparable to granular activated carbons and acid-treated biomass. For example, activated carbon nanofibers against Phenol showed a capacity of 256.1 mg/g (Table 7, N20), and cross-linked cellulose acetate-polybenzoxazine nanofibers demonstrated against Phenantrene 98.5% removal (Table 20, N1) [61,113]. Such a nanofiber web presented adequate structural and chemical surface characteristics for the adsorption of organic contaminants.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature , electrospinning of continuous CA nanofibers without beads used by a single solvent is not reported due to a wide range of technical challenges. Therefore, a variety of binary solvents with various ratios has been used such as Ac:water (3:1 and 4:1) , acetic acid:water (3:1) , acetic acid:Ac (1:1) , Ac:dimethyl sulfoxide (DMSO) (2:1) , dichloromethane (DCM):Ac (1:1, 3:1, and 5:1) , DMAc:DMSO (55:45) , Ac:DMAc (2:1) , and DCM: methanol (4:1) . In this work, it was found that the CA solution for the first time could be continuously electrospun nanofibers using binary solvents of Ac:DMAc (3:1).…”
Section: Resultsmentioning
confidence: 99%